Cognitive biases in cardiology practice from the perspective of evolutionary explanation - G. A. Chasovskikh; E. O. Taratukhin (Кардиоваскулярная терапия и профилактика)
The article examines the impact of cognitive biases on decision-making in cardiology practice and their evolutionary explanations. Cognitive biases are systematic thinking errors that, despite their evolutionary adaptiveness in the phylogeny of humans as a species, can lead to serious mistakes in medical diagnosis, treatment, and patient communication. Research indicates that the influence of cognitive biases can be observed across all medical fields. However, the specific types and manifestations of these biases can vary significantly. In cardiology, physicians are particularly prone to biases such as the availability heuristic, anchoring effect, framing effects, and overconfidence bias. Patients exhibit a heightened vulnerability to the affect heuristic and optimism bias. This study, employing an evolutionary descriptive framework, offers some recommendations for overcoming clinical bias in patient interactions and highlights the potential for practice-oriented research on this topic, especially regarding the cultural and institutional specificities of healthcare in Russia.